Enseigner nos langues maternelles : vecteurs de progrès et d’union des peuples maghrébins - Aous, Rachid (Revue CMC Review, 2016)
In support of the Manifesto for a Political Union of the Peoples of North Africa (U.P.A.N.), Rachid Aous proposes a pedagogy for teaching the maternal languages of the three North African countries, Algeria, Morocco, and Tunisia, including local dialects and Amazigh, to mitigate the concentration on classical Arabic.